2006
DOI: 10.1159/000098039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Estradiol on Glycemic and CNS Neuronal Activational Responses to Recurrent Insulin-Induced Hypoglycemia in the Ovariectomized Female Rat

Abstract: Recurrent insulin-induced hypoglycemia (RIIH) results in glucose counterregulatory dysfunction in men and male rodents. Intensified hypoglycemia in the latter coincides with diminished neuronal Fos expression in central metabolic regulatory structures, evidence that supports habituation of CNS-mediated compensatory motor outflow during re-exposure to this metabolic stress. In light of the evidence for counterregulatory resistance to precedent hypoglycemia in women, we utilized estradiol-treated ovariectomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 40 publications
2
31
1
Order By: Relevance
“…This study did not affirm our prediction of parallelism of adaptation of A2 nerve cell DβH protein expression and DVC Fos immunolabeling (Nedungadi et al 2006) in both estradiol-and oil-implanted OVX rats. Rather, evidence for divergence of these two parameters, independent of estradiol status, detracts from our working assumption that hypoglycemia-induced DVC Fos immunoreactivity is a reliable indicator of metabolo-sensory neuron signaling.…”
Section: Acclimation Of A2 Neuron Dβh Enzyme Protein Expression To Hycontrasting
confidence: 99%
See 1 more Smart Citation
“…This study did not affirm our prediction of parallelism of adaptation of A2 nerve cell DβH protein expression and DVC Fos immunolabeling (Nedungadi et al 2006) in both estradiol-and oil-implanted OVX rats. Rather, evidence for divergence of these two parameters, independent of estradiol status, detracts from our working assumption that hypoglycemia-induced DVC Fos immunoreactivity is a reliable indicator of metabolo-sensory neuron signaling.…”
Section: Acclimation Of A2 Neuron Dβh Enzyme Protein Expression To Hycontrasting
confidence: 99%
“…Estradiol delivery to the ovariectomized (OVX) female rat caudal hindbrain sustains uniformity of glycemic responses to repeated insulin dosing while vehicle controls exhibit delayed recovery from recurring hypoglycemia (Nedungadi and Briski 2012). Moreover, estradiol prevents habituation of hypoglycemia-associated nerve cell Fos immunostaining in the DVC (Nedungadi et al 2006). Estradiol may thus prevent cellular energy state adjustments over serial hypoglycemic bouts or, alternatively, may mask acquired cellular energy instability by promoting signals of energy balance.…”
Section: Introductionmentioning
confidence: 99%
“…Beginning on day 1, the animals in each group were injected with an intermediate-release formulation of insulin or diluent according to the following schedule: (1) subcutaneous injection of diluent on days 1–4 (n = 6); (2) subcutaneous injection of diluent on days 1–3, followed by 12.5 U/kg Humulin NPH (NPH) on day 4 (n = 6); (3) subcutaneous injection of NPH on days 1–3, followed by diluent on day 4, or (4) subcutaneous injection of NPH on days 1–4 (n = 6). We have reported [24] that this dose of NPH decreases the blood glucose levels from approximately 120 to 40 mg/dl in both EB- and oil-implanted OVX rats and that glycemic and central neuronal activational responses to one versus repeated injections were equivalent in the presence of estrogen, whereas hypoglycemia was amplified and the patterns of CNS Fos immunolabeling were diminished in the absence of this hormone.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence that RIIH attenuates genomic reactivity of neurons located in key autonomic metabolic structures in the male but not female rat brain is consistent with a central neural component of this gender-specific response desensitization [7, 8]. We have developed an experimental model for RIIH based upon serial subcutaneous (sc) injection of the therapeutic intermediate-release insulin, neutral protamine Hagedorn (NPH), in order to replicate route of delivery, frequency of administration, and duration of action in the clinical setting.…”
Section: Introductionmentioning
confidence: 82%
“…The present studies utilized a model for recurrent insulin-induced hypoglycemia established and reported by our laboratory, which is characterized by exacerbated hypoglycemia, impaired glucagon and adrenomedullary catecholamine secretion, and attenuated CNS neuronal transcriptional activation in male rats [7]. In contrast, we have reported that female rats exposed to RIIH exhibit estrogen-dependent uniformity of glycemic and Fos protein responses to acute and recurring IIH [8]. For quantitative real-time RT-PCR analyses, animals of both genders were injected sc with the intermediate-release insulin formulation, humulin NPH (12.5 U/kg b.w.…”
Section: Methodsmentioning
confidence: 99%